Thorns Covered in Petals on a Pedestal: A Collection of Lyrical Poetry Exploring the Cause and Effects of Toxic Female Friendship¬ - Hsie Michiko Sachi; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2024)
When a female friend envies and covets what her female friend has, this leads to a toxic female friendship. Toxicity among female friends has its effects on the victims. This leads the victim to normalize toxic friendship behavior, experience loneliness, and have lower self-worth compared to people who are not the victim of the said phenomenon. This creative work is written in a collection of lyrical poetry, portraying the cause and effects of toxic female friendship. There are fifteen poems in total, with six poems portraying the perpetrator’s envy (‘PART I: Side-eyes on Shiny Emblems’) and another nine poems expressing loneliness and lower self-worth of the victim (‘PART II: Lone to the Bone, Too Gloom to Bloom’). This creative work, ‘Thorns Covered in Petals up on a Pedestal’ shows how vicious a hint of envy can be, thus the terrible outcomes it brings in a friendship among females, especially to the victim.